Role of karyopherin nuclear transport receptors in nuclear transport by nuclear trafficking peptide - Teratake, Yoichi; Kimura, Yayoi; Ishizaka, Yukihito (Experimental cell research, 2021)
Nuclear trafficking peptide (NTP), a cell-penetrating peptide (CPP) composed of 10 amino acids (aa) (RIFIHFRIGC), has potent nuclear trafficking activity. Recently, we established a protein-based cell engineering system by using NTP, but it remained elusive how NTP functions as a CPP with nuclear orientation. In the present study, we identified importin subunit β1 (IMB1) and transportin 1 (TNPO1) as cellular proteins underlying the activity of NTP. These karyopherin nuclear transport receptors were identified as candidate molecules by liquid chromatography/mass spectrometry analysis, and downregulation of each protein by small interfering RNA significantly reduced NTP activity (P < 0.01). Biochemical analyses revealed that NTP bound directly to both molecules, and the forced expression of an IMB1 fragment (296–516 aa) or TNPO1 fragment (1–297 aa), which both contain binding sites to NTP, reduced nuclear NTP-green fluorescent protein (GFP) levels when it was added to cell culture medium. NTP is derived from viral protein R (Vpr) of human immunodeficiency virus-1, and Vpr enters the nucleus and exerts pleiotropic functions. Notably, Vpr bound directly to IMB1 and TNPO1, and its function was significantly impaired by the forced expression of the 296–516-aa fragment of IMB1 and 1–297-aa fragment of TNPO1. Interestingly, NTP completely blocked the physical association of Vpr with IMB1 and TNPO1. Although the nuclear localization mechanism of Vpr remains unknown, our data suggest that NTP functions as a novel nuclear localization signal of Vpr.